TIME, LITERATURE AND TRANSLATION: a shared cosmopolitanism - Gonçalves, Davi (Ciência & Trópico, 2018)
The purpose of this article is to deconstruct the narrative of Sunshine sketches of a little town (LEACOCK, 1912) as to make out what might be hidden in-between the jokes told by its narrator. Stories do not only tell us things objectively nor linearly, but are successively asking us to reflect upon what they are not effectively saying. This is what allows our reconsideration about our relationship with meanings external to us – the meanings “we have not seen coming”. Translating would be, thereby, analogous to some sort of reverse time travel: the journey from my nowhere to the direction of the nowhere of the other. If the local colour of Leacock’s (1912) fictional town, Mariposa, is what makes it unique, to generalise its features would be a mistake; regardless of his narrator's assertions, Mariposa is not synonymic to every Canadian town. I am not trying to argue here nonetheless that the local has no relevance to the global, or vice versa; my point is that one does not need to imply the absence of the other, it is their correlation that must be restored.